Pesticide Use, Poisoning, and Knowledge and Unsafe Occupational Practices in Thailand - Ratana Sapbamrer (2018)
© The Author(s) 2018. The agricultural system in Thailand has shifted from a traditional to a commercial agricultural system. Pesticides have been imported into Thailand to increase agricultural productivity, resulting in adverse health effects for farmers and consumers. However, the scientific data available in Thailand are limited and inconsistent. Thus, this article reviews research studies regarding pesticide use, poisoning, and knowledge and unsafe occupational practices in Thailand over the last decade. This article also makes recommendations for future policies. Research studies conducted in Thailand during 2006–2017 were reviewed and summarized. Overall, there are several solutions to address the pesticide problem, such as rigorous legislation and regulations, campaigns for reducing pesticide use, education, and training. The Thai government has an important role in making policies and regulations and encouraging all agricultural activities to be sustainable.